Solo Cup in 2007 : dollars in the details - Shein, James B., 1942-; Frazzano, Rebecca; Meagher, Evan (London : SAGE Publications Ltd, 2017)
The case discusses the operational, strategic, and financial turnaround at Solo Cup, a manufacturer of disposable dining wares. Solo Cups troubles were compounded by the acquisition of a larger rival, Sweetheart Company, which had its own problems and presented issues of merger integration that management could not solve. David Garfield, a managing director at turnaround consulting firm Alix Partners, must first recognize Solo Cups core competencies in order to determine the appropriate change in strategic course, strip out the assets that no longer support the operations necessary for that strategy, and monetize them in order to rationalize its balance sheet. This case teaches that a three-pronged approach will invariably produce greater results than any one-dimensional turnaround.
Originally published: Shein, J., Frazzano, R., & Meagher, E. (2010). Solo Cup in 2007: Dollars in the details. 5-210-261. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Solo Cup Company -- Case studies; Plastics industry and trade -- United States -- Case studies; Paper products industry -- United States -- Case studies; Drinking cups -- History -- Case studies